Про причини, які зумовлюють межі ареалів видів рослин - Melnik, V.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
The state of the problem of decision causes of limits of plant species areas from Alphonse de Candolle to our days are regarded. Contribution of well-known phytogeographes P.P. Semjonov-Tjan-Shanskij, W. Szafer, H. Walter and D. Pigott in solution of this problem are elucidated. Critical analysis of theories and field studies does not confirmed hypothesis about dependence of area limits from the sums of temperatures during vegetative period and isotherms. Determination of influence of ecological (mainly climatic) factors on reproductive processes and forming new generations of plants in populations is a key aspect of investigation of causes of area limits. Reliable determination of causes of plant area limits will be possible only owing to detailed analysis of specific conditions of habitats, study interactions among ecological factors and plants in adult state, as well in initial stages of ontogenesis, take into account plant cultivation within and outside of natural areas.